Edukasi Inovatif Pengolahan Kelor: Moringa Dimsum sebagai Camilan Sehat Berbasis Potensi Lokal - Ayu, Citra; Sari, Putri Krisma; Sari, Windi Riana; Sari, Rizka Nanda; S, Noprina Brielitha; Manalu, Camelia; Sakinah, Sakinah; Mulyani, Rizka Dwi; Yaprianti, Maria; Novia, Merry; Melisa, Melisa (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Moringa oleifera leaves are highly nutritious and have great potential to be developed into functional foods. In Salo Timur Village, moringa has traditionally been used in simple dishes, but innovative modern products such as dim sum have not been widely explored. This community service activity aimed to educate local residents on how to process moringa leaves into a healthy snack called Moringa Dimsum, as a form of nutritious and economically valuable food diversification. The method used was descriptive qualitative with a participatory educational approach based on a case study. The activity did not involve hands-on practice by participants, but rather focused on presentations by a guest speaker, interactive discussions, and the distribution of recipes and product testers. The results showed that participants responded positively to the introduced recipe, recognized its nutritional benefits, and saw its potential as a home-based business opportunity. The program also produced a recipe book titled Moringa Dimsum as a form of documentation and dissemination of local food innovation. This educational activity proved effective in raising nutritional awareness and opening up economic opportunities based on local resources.